2022
DOI: 10.1212/nxi.0000000000200011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effectiveness of IVIg Maintenance Therapy in 36 Patients With GAD Antibody–Positive Stiff-Person Syndrome

Abstract: Background and ObjectivesIVIg has been the preferred immunotherapy in stiff-person syndrome (SPS) based on a 3-month controlled trial, but whether it is also effective in inducing long-term benefits or arresting disease progression is unknown. The information is needed because SPS is a progressively disabling disease and IVIg is liberally used as chronic therapy without efficacy data. The present study explores the long-term effects of IVIg in the largest cohort of well-characterized patients with SPS followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In this large cohort, 24 of the 36 patients (67%) had a clinically meaningful response over a median 3.3 (range 1-18) year period exhibiting improved gait, posture, and balance and also decreased stiffness, spasms, and startle response; some wheelchair-bound patients and those ambulating with devices walked unassisted. 47 Among the responders, 37.5% had longterm stability without disease progression for 4.3 (range 1-18) year period; the other 29.1%, however, although continued to experience improvement, they also exhibited diminishing benefits after a mean 3.3 year period due to disease progression highlighting the need for more effective long-term therapies. 47 Of interest, 12.5% exhibited a conditioning effect after 5 (range 2-18) years emphasizing the need to perform periodic dependency trials during chronic therapy to avoid overuse, as stressed in other neurologic disorders on chronic IVIG therapy.…”
Section: Intravenous Immunoglobulinmentioning
confidence: 93%
See 3 more Smart Citations
“…In this large cohort, 24 of the 36 patients (67%) had a clinically meaningful response over a median 3.3 (range 1-18) year period exhibiting improved gait, posture, and balance and also decreased stiffness, spasms, and startle response; some wheelchair-bound patients and those ambulating with devices walked unassisted. 47 Among the responders, 37.5% had longterm stability without disease progression for 4.3 (range 1-18) year period; the other 29.1%, however, although continued to experience improvement, they also exhibited diminishing benefits after a mean 3.3 year period due to disease progression highlighting the need for more effective long-term therapies. 47 Of interest, 12.5% exhibited a conditioning effect after 5 (range 2-18) years emphasizing the need to perform periodic dependency trials during chronic therapy to avoid overuse, as stressed in other neurologic disorders on chronic IVIG therapy.…”
Section: Intravenous Immunoglobulinmentioning
confidence: 93%
“…47 Among the responders, 37.5% had longterm stability without disease progression for 4.3 (range 1-18) year period; the other 29.1%, however, although continued to experience improvement, they also exhibited diminishing benefits after a mean 3.3 year period due to disease progression highlighting the need for more effective long-term therapies. 47 Of interest, 12.5% exhibited a conditioning effect after 5 (range 2-18) years emphasizing the need to perform periodic dependency trials during chronic therapy to avoid overuse, as stressed in other neurologic disorders on chronic IVIG therapy. 43 Based on these 2 large short-term and long-term studies, IVIg is effective in SPS and remains a key immunomodulatory therapy with proven benefit requiring, however, a judicious use for chronic maintenance to avoid overuse and conditioning effects.…”
Section: Intravenous Immunoglobulinmentioning
confidence: 93%
See 2 more Smart Citations
“…Her current functional status is overall improved from her nadir dysfunction with maintenance IVIg, and hence, this immune therapy will be continued in conjunction with her symptomatic interventions. In fact, a recent study demonstrated that maintenance IVIg can be a durable treatment for patients with SPS (17).…”
Section: Dr Newsome (Neuroimmunology)mentioning
confidence: 99%